2008
DOI: 10.1123/ijsnem.18.6.617
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Fasting’s Effect on Plasma Leptin, Adiponectin Concentrations, and Body Composition in Trained Young Men

Abstract: Lipolysis might have occurred because of increased plasma triglycerides and HDL cholesterol concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 29 publications
5
36
3
2
Order By: Relevance
“…6) For cortisol, Al-Hadramy et al reported a reduction and Bahijri et al reported an increase in concentrations (10,11). 7) With respect to renal parameters, conflicting urea concentrations have been reported (2,3,7), and Maislos et al found no significant changes regarding creatinine concentrations (7). Several studies showed a reduction (3,8,12), and other studies no change, in body weight or body mass index (BMI) (4,13) during Ramadan fasting.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…6) For cortisol, Al-Hadramy et al reported a reduction and Bahijri et al reported an increase in concentrations (10,11). 7) With respect to renal parameters, conflicting urea concentrations have been reported (2,3,7), and Maislos et al found no significant changes regarding creatinine concentrations (7). Several studies showed a reduction (3,8,12), and other studies no change, in body weight or body mass index (BMI) (4,13) during Ramadan fasting.…”
Section: Introductionmentioning
confidence: 99%
“…7) With respect to renal parameters, conflicting urea concentrations have been reported (2,3,7), and Maislos et al found no significant changes regarding creatinine concentrations (7). Several studies showed a reduction (3,8,12), and other studies no change, in body weight or body mass index (BMI) (4,13) during Ramadan fasting. 8) Blood pressure during Ramadan fasting has been found unchanged (14), or systolic as well as diastolic blood pressures were reported decreased (15).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations